2001
DOI: 10.1016/s0736-0266(00)00060-7
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids alter the differentiated phenotype of articular chondrocytes

Abstract: Experimental evidence suggests that recommended dosages of some corticosteroids used clinically as antiinflammatory agents for treating arthropathies damage articular cartilage, but low dosages may be chondroprotective. The purpose of this study was to evaluate how different concentrations of methylprednisolone affect chondrocyte function and viability. Articular cartilage and chondrocytes were obtained from young adult horses, 1 5 3 . 5 years of age. Corticosteroid-induced changes in collagen expression were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 39 publications
1
45
0
3
Order By: Relevance
“…Intraarticular injection of corticosteroid is an effective and common treatment for osteoarthritis, although clinical evidence suggests it provides a relatively short-lived benefit in pain relief [16,21,26,27,37,42,44,47]. One study suggested certain dosages of corticosteroids used clinically as antiinflammatory drugs for osteoarthritis are harmful to articular cartilage [15], whereas lower dosages are reportedly chondroprotective and delay progression of cartilage lesions [8,28,36,38,43]. In vitro we found betamethasone and prednisolone had no effect in inducing chondrocyte cell death when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraarticular injection of corticosteroid is an effective and common treatment for osteoarthritis, although clinical evidence suggests it provides a relatively short-lived benefit in pain relief [16,21,26,27,37,42,44,47]. One study suggested certain dosages of corticosteroids used clinically as antiinflammatory drugs for osteoarthritis are harmful to articular cartilage [15], whereas lower dosages are reportedly chondroprotective and delay progression of cartilage lesions [8,28,36,38,43]. In vitro we found betamethasone and prednisolone had no effect in inducing chondrocyte cell death when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The possible longterm effects and the unpredictable duration are controversial and matters of debate [13,48]. Repeated use of corticosteroids especially could facilitate tissue atrophy, joint destruction, or cartilage degeneration [9,15,35].…”
Section: Introductionmentioning
confidence: 99%
“…Farkas et al (32) reported that glucocorticoids and local anesthetics induced apoptosis in chondrocytes especially in the superficial layer of the osteochondral specimens. Fubini et al (33) also suggested that methylprednisolone suppressed matrix protein markers of chondrocytic differentiation and that the altered chondrocyte expression of matrix proteins likely contributed to the pathogenesis of corticosteroid-induced cartilage degeneration. On the other hand, Vos et al (34) reported that the plasma level of human cartilage glycoprotein was increased in inflammatory conditions such as SLE with and without joint disease.…”
Section: Discussionmentioning
confidence: 99%
“…Triamcinolone, a commonly used intraarticular corticosteroid [8,42], is clinically nondeleterious [37]. Although some studies show slowing of mechanically and chemically induced degeneration on a gross level [33,34,43], others have found histologic evidence of chondrotoxicity from corticosteroids in experimental models [7,19,32,39]. However, these studies did not evaluate buffering of the reagents to a physiologic pH and they were not performed on human cartilage.…”
Section: Introductionmentioning
confidence: 99%